Students’ accommodation allocation: a multicriteria decision support system - Rasoanaivo, Rôlin Gabriel (2022)
The social life of students at university has an impact on their educational success. The allocation of accommodation is part of this aspect. This article presents our proposal to improve students’ allocation accommodation. We aim to support university administrative departments for the selection of students for housing. Therefore, we propose a decision support system based on multi-criteria decision support methods. To calculate the weights of the criteria, we use the Analytic Hierarchy Process (AHP) method. Then, to rank the students, Analytic Hierarchy Process, Weighted Sum Method (WSM) and Preference Ranking Organisation Method for Enrichment Evaluation methods (PROMETHEE) are used. The aim is to find the most adequate method to rank the students. The result is achieved because the AHP can calculate the weight of criteria and the AHP, WSM and PROMETHEE are able to rank the students.